Nothing Lasts Forever: A Children Book About the Loss of Attachment - Kevin Rahardja; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
The loss of an attachment figure, whether a person, pet, or place, is a profound challenge that destabilizes a child's sense of security. This paper explores the creation of Nothing Lasts Forever, a series of five picture books designed to help children navigate grief using magical realism and John Bowlby’s attachment theory. The work demonstrates that loss manifests functionally as protest (anger and denial) and despair (withdrawal), which are necessary distress signals. By utilizing a creative practice-based methodology, the project illustrates how a caregiver’s support as a "safe haven" and "secure base" allows children to form continuing bonds. Grounded in psychological principles, this series serves as a therapeutic tool for fostering emotional resilience.